The effects of a mixture of small peptide chelating minerals and inorganic minerals on the production performance and tissue deposition of broiler chickens - Han, Xiaofeng; Kong, Jing; Zheng, Chaojun; Yan, Xia; Qiu, Ting; Chen, Zhiyong; Zhang, Huihua (Frontiers in Veterinary Science, 2024)
Due to the limited bioavailability of inorganic trace minerals, their utilization in poultry production has led to problems such as environmental contamination and inefficient resource utilization. It was investigated whether replacing inorganic trace minerals (ITM) with a blend of organic small peptidechelated trace minerals (MIX) would improve production performance, selected biochemical parameters, antioxidant capacity, mineral deposition in liver, heart, and tibia, as well as mineral content in feces of broilers. A total of 432 healthy 21-day-old 817 broilers were randomly divided into 4 groups with 6 replicates per group and 18 chickens per replicate. The control group received a basal diet supplemented with 1000 mg/kg of inorganic trace minerals as sulfate. The experimental groups received basal diets supplemented with 200, 400, and 600 mg/kg of mixed trace mineral elements (50% sulfate + 50% small peptide-chelate) for a trial period of 30 days, divided into two stages: 21-35 days and 36-50 days. The results indicate that on the 50th day, compared with the 1000 mg/kg ITM group, the levels of serum cholesterol, urea nitrogen, and malondialdehyde in the 200, 400, and 600 mg/kg MIX groups decreased (P<0.01), while the levels of serum glutathione peroxidase in the 200, 400, and 600 mg/kg MIX groups increased (P<0.05). Compared to the ITM group, the addition of organic small peptide chelated trace minerals mixed with inorganic trace minerals can reduce the levels of zinc and manganese in feces (P<0.01). Furthermore, the iron content in the heart and tibia of the 600 mg/kg MIX group also significantly decreased (P<0.05). There were no differences in growth performance and slaughter performance among the groups (P>0.05). This study shows that replacing inorganic minerals with low-dose MIX (200, 400, and 600 mg/kg) can reduce the levels of zinc and manganese in feces, with no negative impact on growth and slaughter performance.